Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5539/ijef.v4n9p34
|View full text |Cite
|
Sign up to set email alerts
|

Residential Location Choice: The Role of a Taste for Similarity

Abstract: This paper examines the importance of social interactions on a household's location decision. The theory argues that individuals' utility will be greater when socially interacting with similar others. The hypothesis that a household desires to find a good community match is tested through the application of a discrete residential location choice model. In addition, this paper also tests Tiebout's hypothesis that households search for a community where their benefits from local public goods will exceed their lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…From the empirical variogram/semivariogram, the parameters of a fitted variogram/semivariogram function can be estimated. Kiefer (2007) applied a spherical semivariogram function to form school district price indices within Franklin County, OH. 5 Ideally, the measure of ''neighborhood effect'' should reflect all houses in the given neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…From the empirical variogram/semivariogram, the parameters of a fitted variogram/semivariogram function can be estimated. Kiefer (2007) applied a spherical semivariogram function to form school district price indices within Franklin County, OH. 5 Ideally, the measure of ''neighborhood effect'' should reflect all houses in the given neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have some similarities and differences with the results emerging from the developed countries. The variables of neighborhood-related attributes such as nice neighborhood [3,18,24], presence of family, social contacts, and people having similar socioeconomic status [14], etc., have also been reported as a significant determinant of residential location choices in the developed world. However, the role of gender and housing tenure in deciding the residential self-selection in developing countries is different than the results surfacing from the studies conducted in the developed world.…”
Section: Discussionmentioning
confidence: 99%
“…Morency and Verreault (2020) found that a well-considered residential location choice can considerably reduce the commuting distances and as a result could also cause increasing walking, cycling, and public transport trips [13]. In some of the studies conducted in the developed world, social interactions and neighbors with similar socioeconomic backgrounds have also been a significant factor in residential location choices [14]. Other important determinants of residential location choices have been reported as the quality of schools [15], accessibility to services and jobs [16,17], mobility attitudes, the built environment [18][19][20][21][22], and the affordability and neighborhood characteristics [23,24].…”
Section: Correlates Of Residential Location Choicesmentioning
confidence: 99%